Mycelial DNA persistence in a forest soil. Issue 6 (4th August 2021) - Gordon, Matthew; Van Norman, Kelli
Abstract: Living fungi can be identified and monitored in their soil habitat using an array of molecular methods. However, DNA originating from dead fungal tissue may become stabilized in the soil and remain detectable for some time after cell death rendering species detections with molecular methods difficult to interpret. Very little data exist about the persistence time of DNA from dead mycelium as it decomposes within the soil ecosystem. We placed soil containing the heat‐killed mycelium of two mycorrhizal fungal species, Phaeocollybia scatesiae A.H. Sm. & Trappe and P . fallax A.H. Sm., in mesh bags and buried them at a forested site in the Oregon Coast Range. The detectability of Phaeocollybia DNA in the soil bags was monitored over 8 months using PCR with species‐specific primers. We found that after 2 months of burial, P . scatesiae was undetectable, while P . fallax was barely detected. No Phaeocollybia DNA was detected at 3 months or thereafter. With the determination of this fungal DNA persistence time, treatment effect studies with an appropriate post‐treatment waiting period can be designed. The applicability of this fungal DNA persistence time to other studies depends on many factors, but we provide a reference point for the soil/ fungus environmental DNA system where very few exist. Abstract : Oregon Coast Range study site habitat (left), Phaeocollybia scatesiae sporocarps (upper right), Phaeocollybia fallax sporocarps (lower right).